2008
DOI: 10.1021/je800348s
|View full text |Cite
|
Sign up to set email alerts
|

Densities and Viscosities of Binary Mixtures of JP-10 with n-Octane or n-Decane at Several Temperatures

Abstract: The densities and viscosities of the binary mixtures of JP-10 + n-octane and JP-10 + n-decane were determined from T = 293.15 K to T = 313.15 K at atmospheric pressure, over the entire composition range. Excess volume V m E of the binary mixtures was calculated. The experimental data indicate that the addition of n-alkane has a distinct effect on the density and viscosity of JP-10, and V m E values of the binary systems are negative. Experimental data were fitted to the Redlich−Kister equation, and the adjusta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…The single-component hydrocarbon fuel Jet Propellant-10 (JP-10) is used in detonation engines, missiles, and supersonic combustion ramjets, where a fuel is required to have high thermal stability, high-energy density, and low freezing point. Because of its broad applications, the principal constituent of JP-10, tricyclo­[5.2.1.0 , ]­decane ( exo -tetrahydrodicyclopentadiene; exo -TCD; C 10 H 16 ; Figure ), has attracted significant attention of researchers, and numerous experimental, theoretical, and modeling studies of its pyrolysis and combustion have been reported in the literature. A detailed overview on the JP-10 studies was provided in our recent publication, and here we only briefly reiterate its key points.…”
Section: Introductionmentioning
confidence: 99%
“…The single-component hydrocarbon fuel Jet Propellant-10 (JP-10) is used in detonation engines, missiles, and supersonic combustion ramjets, where a fuel is required to have high thermal stability, high-energy density, and low freezing point. Because of its broad applications, the principal constituent of JP-10, tricyclo­[5.2.1.0 , ]­decane ( exo -tetrahydrodicyclopentadiene; exo -TCD; C 10 H 16 ; Figure ), has attracted significant attention of researchers, and numerous experimental, theoretical, and modeling studies of its pyrolysis and combustion have been reported in the literature. A detailed overview on the JP-10 studies was provided in our recent publication, and here we only briefly reiterate its key points.…”
Section: Introductionmentioning
confidence: 99%
“…It is a candidate fuel for supersonic aircraft and hypersonic missile. A large amount work have been put into investigating the thermophysical properties of JP-10 including density, viscosity, heat capacity, vapor pressure, and speed of sound, etc. as well as its thermal and chemical stability which is necessary for its application.…”
Section: Introductionmentioning
confidence: 99%
“…Our group [12][13][14][15][16][17][18][19] has performed fundamental research on the thermal oxidation stability, physical properties, and catalytic cracking of JP-10 under different conditions. The experimental results we obtained indicate that the predominant hydrocarbon products of catalytic cracking are methane, ethane, ethene, propane, and propylene in the gaseous phase, and benzene, indene, naphthalene, and their homologs in the liquid phase.…”
Section: Introductionmentioning
confidence: 99%